Handbook of Performability Engineering
DOI: 10.1007/978-1-84800-131-2_58
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Reliability and Failure Mode Analysis of Microelectromechanical Systems (MEMS)

Abstract: Abstract:The reliability issues concerning on microelectromechanical systems (MEMS) have steadily developed in recent years. One of the processes to understand MEMS reliability is to know the failure modes of these microdevices. In this chapter, we seek to report on both well known and unknown failure modes of MEMS. Most of the failure patterns are the same in nanoelectromechanical systems (NEMS), because NEMS followed a developmental path similar to that of MEMS in functional design, materials, and fabricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…A complete loss of signal can also be represented by this type of fault by assuming that the output from the sensor is zero (i.e., δ = 0). There has been considerable research into specific failure mechanisms of individual types of MEMS sensors [10][11][12][13][14][15][16]. However information regarding operational failure modes in MEMS and how the mechanisms described in the literature link to the functional failures (bias, drift, scaling and hard failure) is lacking [16].…”
Section: Scope Of the Management Systemmentioning
confidence: 99%
“…A complete loss of signal can also be represented by this type of fault by assuming that the output from the sensor is zero (i.e., δ = 0). There has been considerable research into specific failure mechanisms of individual types of MEMS sensors [10][11][12][13][14][15][16]. However information regarding operational failure modes in MEMS and how the mechanisms described in the literature link to the functional failures (bias, drift, scaling and hard failure) is lacking [16].…”
Section: Scope Of the Management Systemmentioning
confidence: 99%
“…These parts are subject to degradations and failure mechanisms due to several factors (temperature, humidity, vibration, moisture, noise, electrical overloads, etc.). Common failure mechanisms identified and known until now concern stiction, wear, fracture, crystallographic defect, creep and degradation of dielectrics [6,7,8,9]. The reliability of these microsystems is then considered as a major obstacle in their development [10].…”
Section: State Of the Artmentioning
confidence: 99%
“…Always in the same category, a review of MEMS reliability issues and failure mechanisms can be found in [13]. The chapter published in [9] reported known and unknown failure modes of…”
Section: Reliability Reviewsmentioning
confidence: 99%
“…The difficulty in ensuring proper MEMS behavior and maintenance of their functions in routine circumstances emanates from the limited information about the microscopic failure mechanisms (low cycle fatigue, stress corrosion, adhesion, etc) [2]. From an engineering point of view, the typical failure modes are treated as system parameters variations and faults causing abnormal systems performance.…”
Section: Introductionmentioning
confidence: 99%